On Statistical Convergence in Credibility Space. (11th June 2022) - Savaş, Ekrem; Kişi, Ömer; Gürdal, Mehmet
Abstract: In this paper, we present the notions of statistically convergent sequence for fuzzy variables, statistically Cauchy sequence in credibility space, and present a kind of statistical completeness for credibility space. Furthermore, the conditions of statistical convergence almost surely (a.s.), statistical convergence in credibility, statistical convergence in mean, statistical convergence in distribution and statistical convergence uniformly almost surely (u.a.s.) of fuzzy variable sequences are examined. We have proved relations between these notions.